Analisis Diallel Untuk Daya Gabung Tanaman Jagung (Zea mays L.) Pada Tiga Tingkat Kerapatan Tanam (Diane] Analysis For Combining Ability of Corn (Zea mays L.) at Three Plant Densities). - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1991)
The objective of this study was to estimate general combining ability (GCA) and specific combining ability (SCA) of six inbreds of maize at three plant densities. These six inbreds were crossed in diallel method. 15 hybrids derived from these crosses were evaluated at three levels of population densities (35,714